2015
DOI: 10.2147/ott.s82174
|View full text |Cite
|
Sign up to set email alerts
|

Decreased pretreatment lymphocyte/monocyte ratio is associated with poor prognosis in stage Ib1–IIa cervical cancer patients who undergo radical surgery

Abstract: BackgroundRecently, pretreatment monocyte counts and the lymphocyte/monocyte ratio (LMR) have been proven to be significantly associated with the clinical outcomes of several types of cancer. In this study, we analyzed the prognostic significance of the LMR in stage Ib1–IIa cervical cancer patients who underwent a radical operation.MethodsA total of 485 patients with stage Ib1–IIa cervical cancer were included in this retrospective study. We evaluated the prognostic values of the absolute lymphocyte count, abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“… 31 Chen et al evaluated the prognostic values of LMR in 485 patients with stage Ib1–IIa cervical cancer and found that decreased pretreatment LMR is associated with a poor prognosis in stage Ib1–IIa patients who undergo a radical operation. 33 In the present study, we analyzed 144 patients who underwent curative operation for primary pancreatic adenocarcinoma, and found that LMR was not only an independent prognostic factor of primary pancreatic adenocarcinoma but also significantly related to TNM stage, which coincides with previous studies.…”
Section: Discussionsupporting
confidence: 90%
“… 31 Chen et al evaluated the prognostic values of LMR in 485 patients with stage Ib1–IIa cervical cancer and found that decreased pretreatment LMR is associated with a poor prognosis in stage Ib1–IIa patients who undergo a radical operation. 33 In the present study, we analyzed 144 patients who underwent curative operation for primary pancreatic adenocarcinoma, and found that LMR was not only an independent prognostic factor of primary pancreatic adenocarcinoma but also significantly related to TNM stage, which coincides with previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Despite inconsistent results, these markers have been reported to have significant diagnostic and prognostic value in a wide variety of cancers. The MLR has been suggested to be associated with survival in patients with malignant lymphomas and many solid tumors, such as head and neck, breast [14], lung, esophageal, gastric, colorectal [15], [16], pancreatic, bladder [6], and cervical cancers [5]. A high MLR was associated with poor OS in previous reports, and the MLR can be considered to be a potential surrogate biomarker in various cancers.…”
Section: Discussionmentioning
confidence: 92%
“…However, the association was not significant in colorectal carcinoma (HR: 0.85, 95% CI: 0.63–1.15; P = 0.301) and other hematological malignancies (HR: 0.74, 95% CI: 0.51–1.06; P = 0.100). Seven studies comprising 1,849 patients reported hazard ratios for RFS [12, 26, 29, 32, 35, 36, 56]. A combined analysis showed that LMR lower than the cutoff was associated with poor RFS in non-hematological malignancy (HR: 0.50, 95% CI: 0.36–0.70; P < 0.001).…”
Section: Resultsmentioning
confidence: 99%